Urban Municipal Solid Waste management: Modeling air pollution scenarios and health impacts in the case of Accra, Ghana - Kanhai, G.; Fobil, J.N.; Nartey, B.A.; Spadaro, J.V.; Mudu, P. (Waste Management, 2021)
Despite the clear link between air pollution and health, research to investigate the relationship between municipal solid waste management and air pollution and health has not been prioritized. Such research may generate scientific information that would help reduce population exposure to air pollutants. This paper examines the case study of Accra in Ghana, a city dealing with serious waste management problems. The paper proposes a methodology to estimate the impact of waste management on urban air pollution and health. The analysis is described in the following four steps: (1) collecting data on the waste sector; (2) modeling the emissions arising from waste management; (3) transforming emissions to concentration values and (4) estimating the burdens on health. The assessment has been conducted using the CCAC SWEET tool and WHO AirQ+. The method presented can be used in different locations, depending on data availability, when analyzing the impact of and potential changes to waste sector policies. The results of this health impact assessment indicate that, based on the emissions of PM2.5 from the waste sector in Accra, a change from the business-as-usual to more sustainable options would reduce air pollutants emissions and avert 120 premature deaths in 2030. Levels of air pollution in Accra are significant and interventions to reduce PM2.5 exposure should be promoted. The detailed analysis of the current situation provides suggestions for waste management policies in terms of impacts on health and ideas to reconsider the waste policies in Accra.
Research Article
Keywords: Solid waste management; Landfills; Waste burning; Air pollution; Health; Accra; SWEET tool; AirQ+